2016
DOI: 10.4103/2278-330x.179696
|View full text |Cite
|
Sign up to set email alerts
|

Malignant and borderline phyllodes tumor of breast treated with a multi-modality approach in a tertiary cancer care centre in North India

Abstract: Background:Phyllodes tumor (PT) of the breast can be categorized into benign, borderline and malignant subgroups depending on various histopathological factors. Although malignant PTs may be indolent and controlled by local excision, they frequently show local and distant relapses. Literature reveals local recurrence to be the predominant pattern of failure and thus emphasizes the importance of adjuvant radiation in these tumors. The role of systemic chemotherapy has remained doubtful.Materials and Methods:We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the past, surgeons generally chose simple or radical mastectomy for borderline and malignant PTs. 23 The study by Hasssouna et al 24 revealed that radical surgery really improved the survival and decreased the rate of local recurrence. In addition, another study by Barth et al 25 showed that the prognosis of wide local excision combined with postoperative radiotherapy was equivalent to that of radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, surgeons generally chose simple or radical mastectomy for borderline and malignant PTs. 23 The study by Hasssouna et al 24 revealed that radical surgery really improved the survival and decreased the rate of local recurrence. In addition, another study by Barth et al 25 showed that the prognosis of wide local excision combined with postoperative radiotherapy was equivalent to that of radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of core needle biopsy (CNB) in diagnosing PTs is 63% while that with (FNAC) is 40% [37]. Wide Local Excision (WLE), with a margin of at least 1 cm is the surgery of choice (S. [21]). Re-excision is indicated when necessary to reduce recurrence rates following excision with inadequate margins.…”
Section: Introductionmentioning
confidence: 99%
“…However, available data indicate that RT will reduce recurrence after breast conserving resection for borderline or malignant PTs. There is less agreement about the role of adjuvant RT when wide margins ⩾ 1 cm can be obtained (S. [21]). Adjuvant chemotherapy should be administered only for a minority of patients with large, high-risk or recurrent malignant tumors, and only after a thorough discussion about the risks and benefits of treatment ( [21]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomal doxorubicin in combination with bevacizumab has been reported in one case 17. In an Indian report, epirubicin with ifosfamide was administered to four patients 18. Due to the rarity of the disease, there is no consensus on the systemic treatment of these tumours and patients are treated according to National Comprehensive Cancer Network (NCCN) and European Society for Medical Oncology (ESMO) sarcoma guidelines 8 9.…”
Section: Introductionmentioning
confidence: 99%